Pengembangan E-Book Interaktif Anti Korupsi Melalui Kegiatan P5 Pada Siswa Sekolah Dasar - Dzikraa Febry Fauzie; Komariah Komariah; Yayang Furi Furnamasari (Jurnal Bintang Pendidikan Indonesia, 2023)
This research is motivated by the problem of corruption, which is currently still the main cause of obstruction of national development. Anti-corruption education as a preventive form of corruption eradication is attempted to build anti-corruption attitudes and understanding of students. Indications that students are infected with corruption are characterized by lying to get benefits and lack of discipline. Seeing the challenges in order to improve the character of students, the P5 program was formed, namely the profile project of strengthening Pancasila students in the independent curriculum. Thus, this research aims to create an interactive learning media in the form of an E-Book with the title "Berani Anti Korupsi" as a facilitator for students to learn anti-corruption education through P5 activities. This research uses the ADDIE model which consists of five stages, namely Analysis (Analyze), Design (Design), Development (Development), Implementation (Implementation) and Evaluation (Evaluation). The results of the assessment obtained through experts and users indicate that the Interactive E-Book media "Brave Anti-Corruption" can be applied as a learning media that supports anti-corruption education in Fourth grade in elementary school.